Respuesta :

Answer:

At Point A, y = 1

At Point B, y = 1/4

At Point C, y = -2

At Point D, x = -3 2/3

Step-by-step explanation:

Given that the equatuon is y = (-3/4)x + 1/4. In the table, you have to find the value of y. In order to find y, you have to substitute x value into the equation :

Point A,

Let x = -1,

y = (-3/4)(-1) + 1/4

= 3/4 + 1/4

= 4/4

= 1

Point B,

Let x = 0,

y = (-3/4)(0) + 1/4

= 1/4

Point C,

Let x = 3,

y = (-3/4)(3) + 1/4

= -9/4 + 1/4

= -8/4

= -2

For Point D, it is slightly different. It have given us the y value so we can just substitute y value into the equation to find x value :

Let y = 3

3 = (-3/4)(x) + 1/4

-3x/4 = 3 - 1/4

= 11/4

-3x = 11/4 × 4

= 11

x = 11 ÷ -3

= -11/3